Transaction costs and informational cascades in financial markets: Theory and experimental evidence. - Marco Cipriani; Antonio Guarino (European Central Bank (ECB), 2007)
We study the effect of transaction costs (e.g., a trading fee or a transaction tax, like the Tobin tax)on the aggregation of private information in financial markets. We analyze a financial market à la Glosten and Milgrom, in which informed and uninformed traders trade in sequence with a market maker. Traders have to pay a cost in order to trade. We show that, eventually, all informed traders decide not to trade, independently of their private information, i.e., an informational cascade occurs. We replicated our financial market in the laboratory. We found that, in the experiment, informational cascades occur when the theory suggests they should. Nevertheless, the ability of the price to aggregate private information is not significantly affected.
Keywords: C92; D8; G14; 330; Herd Behavior; Informational Cascades; Tobin Tax; Trade Costs; Finanzmarkt; Transaktionskosten; Herdenverhalten; Asymmetrische Information